Hiszpańska podróż Jędrzeja Giertycha - Kabaciński, Dawid (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Jędrzej Giertych 1903–1992 was both afamous activist of the National Party as well as a journalist. In 1937 as a war correspondent of „Kurier Poznański”, he went to report on the Spanish Civil War. In this way his famous reports were made. They were published in book Hiszpania bohaterska Heroic Spain. Nowadays, Giertych can be agood example of asubjective journalist. He was a supporter of general Franco. He wrote to show the readers that Franco was right and the left wing Republicans was evil.
Keywords: Giertych, Jędrzej; hiszpańska wojna domowa